Second-chance programs addressing early school leavers: A SWOC analysis of an intervention in a marginalized urban area in Cairo - George, Nada Nabil (AUC Knowledge Fountain, 2016)
The thesis explores the topic of second chance programs that are being provided to early school leavers living in poor urban areas. The purpose of these programs is to enable school learvers to compensate for the skills that were not attained for not going to school. The case study focuses on a program in the garbage village (Zabbaleen area) located in Mokattam area in Cairo, Egypt. This area was chosen because of the high rate of early school leavers, attributed to the requirement of their job (garbage collection) to support their families. The study focuses on a local NGO located in the Zabbaleen area that is providing a second chance program for children living in the same area. The thesis is based on qualitative research method, in the form of in depth interviews with the NGO program staff, field observations of the children attending the classes, and interviews with some of the residents of the area. The study is showing major factors causing dropping out of school, and illustrating several aspects of the second chance program in a form of SWOC analysis (Strength, weaknesses, opportunities and challenges). Strengths identified relate to being formed located in the same Zabbaleen Community, and to getting in close and direct contact with parents and children. As for the weaknesses identified, these relate to the lack of proper communication among other NGOs serving the zabbaleen area, to the finding that some children are dealing with the program as an alternative to schools (not willing to enroll back to school), besides, the inflexible internal regulations and policies. As for the opportunities, the NGO is showing a strong positive engagement with the residents despite their challenging environment in which they live and even positively influencing norms such as gender culture. The last part of the analysis was the challenges of the program which highlight the competition from other NGOs serving the area, the weak collaboration with governmental entities, and the challenges in securing funding to support their major activities.